2005
DOI: 10.1016/s0899-3467(07)60114-1
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of expertise in spinal manipulative therapy using an instrumented manikin

Abstract: (J Chiropr Med 2005;4:53-60)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 20 publications
6
65
0
1
Order By: Relevance
“…Rates of force production values observed in this study were similar to values reported for experts and graduating students with basic clinical experience evaluated with the same instrumented manikin. 13 Although these values are slightly different than those measured when adjusting human subjects, 14,15 they clearly illustrate the level of expertise reached by these participants. In the first stage of learning, preload forces are usually ignored by learners.…”
Section: Discussionmentioning
confidence: 78%
“…Rates of force production values observed in this study were similar to values reported for experts and graduating students with basic clinical experience evaluated with the same instrumented manikin. 13 Although these values are slightly different than those measured when adjusting human subjects, 14,15 they clearly illustrate the level of expertise reached by these participants. In the first stage of learning, preload forces are usually ignored by learners.…”
Section: Discussionmentioning
confidence: 78%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14] More recently, those same tools are being used to augment the learning in chiropractic colleges in the United States and abroad, 11,[15][16][17][18][19][20][21][22][23][24] and in physical therapy programs as well. 25 Preload, peak loads, and speed have all been suggested as important performance factors.…”
Section: Introductionmentioning
confidence: 99%
“…1 It has been characterized by applying a dynamic highvelocity low-amplitude thrust into a specific contact on the patient's body. 2 Chiropractic students learn how to perform this skill during their training years at a chiropractic institution.…”
Section: Introductionmentioning
confidence: 99%
“…2 Chiropractic students learn how to perform this skill during their training years at a chiropractic institution. 1 The format and amount of time spent training to learn spinal manipulation skills can range from formalized curricula in professional programs to weekend seminars and individual demonstrations; however, each chiropractic college teaches core manipulation procedures. 3 In comparison to other professional programs that teach spinal manipulation, such as the doctor of osteopathy, doctor of medicine, and master of physiotherapy programs, doctor of chiropractic programs in both Canada and the United States offers extensive hours of training specifically in the skill of spinal manipulation in order to train chiropractors to be proficient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation